ANALISIS BALANCED SCORECARD PT. PP PROPERTI Tbk (STUDI PADA PROYEK BEGAWAN APARTEMEN KOTA MALANG) - IMAM HANAFI ; Dr. Sudjatno SE., MS
This study aims to determine the performance of PT. PP Properti Tbk in _x000D_ Begawan Apartment project in Malang city in terms of five perspectives of_x000D_ Sustainability Balanced Scorecard which are Finance, Marketing, Internal Business_x000D_ Processes, Growth-Learning, and Social. The type of this research is oreover, this_x000D_ research uses und secondary data with several data collection methods including_x000D_ terviews, questionnaires, literature studies, and documentation. Therefore, the_x000D_ results of this rcsearch can be concluded that PT, PP Praperti Tbk on Begawan_x000D_ Apartment Project has a good performance. Specifically the measurement shows_x000D_ excellent performanccs for the customer perspective, internal business process_x000D_ descriptive rescarch with a case study approach. M primary perspective, Icarning_x000D_ and growth perspective, and social perspective. However, due to the limitation of_x000D_ this rescarch regarding to the financial statement of the project, the results of_x000D_ financial perspective was taken from centralized financial report of PT. PP Properti_x000D_ Tbk which shows the detcrioration of the performance during 2017-2018. _x000D_ _x000D_ _x000D_ Keywords : Balanced Scorecard, Sustainability Balanced Scorecard, _x000D_ Performance Measurement, Financial Perspective, Customer_x000D_ Perspective, Internal Business Process Perspective, Learning and_x000D_ Growth Perspective, Social Perspective